PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PERPINDAHAN MEREK PADA SEPEDA MOTOR YAMAHA DI KOTA SEMARANG (Students' Journal of Economic and Management, 2016)
The aim of this study was to analyze the effect of product quality, price and brand image to brand switching decision on a Yamaha motorcycle in the city of Semarang. The study population was a Yamaha motorcycle users in the city of Semarang. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The criteria for the sample in this study is the consideration of samples in this study were residents of Semarang who use the brand Yamaha for 2 years and have switched to other brands (eg Honda) for 1 year. The analysis tool used is the test of validity, reliability and multiple linear regression. The results of the analysis can be concluded that: The product quality negatively affects brand switching decision. The better the quality of the product, it will lower the brand switching decision. Positive effect on the price of brand switching decision. The higher the price offered, it will increase brand switching decision. Negatively affect the brand image brand switching decision. The better the image of the brand, it will lower the brand switching decision. Keywords: product quality, price, brand image and brand switching decision